Anonymous Real-Time Analytics Monitoring Solution for Decision Making Supported by Sentiment Analysis - Gildásio Antonio de Oliveira Júnior; Robson de Oliveira Albuquerque; César Augusto Borges de Andrade; Rafael Timóteo de Sousa; Ana Lucila Sandoval Orozco; Luis Javier García Villalba (Sensors, 2020)
Currently, social networks present information of great relevance to various government agencies and different types of companies, which need knowledge insights for their business strategies. From this point of view, an important technique for data analysis is to create and maintain an environment for collecting data and transforming them into intelligence information to enable analysts to observe the evolution of a given topic, elaborate the analysis hypothesis, identify botnets, and generate data to aid in the decision-making process. Focusing on collecting, analyzing, and supporting decision-making, this paper proposes an architecture designed to monitor and perform anonymous real-time searches in tweets to generate information allowing sentiment analysis on a given subject. Therefore, a technological structure and its implementation are defined, followed by processes for data collection and analysis. The results obtained indicate that the proposed solution provides a high capacity to collect, process, search, analyze, and view a large number of tweets in several languages, in real-time, with sentiment analysis capabilities, at a low cost of implementation and operation.